Literature Review: The Relationship Between Mothers’ Knowledge of Diarrhea and Diarrhea Prevention Behaviors in Toddlers - Ni Nyoman Sutiari; Cici Cici; Siti Hartina; Sudirman Sudirman; Ahmad Yani (Jurnal Indonesia Sosial Sains, 2026)
Diarrhea remains a major health problem in toddlers, contributing to high rates of child morbidity and mortality. Diarrhea prevention behavior in toddlers is strongly influenced by the mother's role as the primary caregiver, especially the mother's level of knowledge about diarrhea. This research aims to analyze the relationship between the mother's level of knowledge about diarrhea and diarrhea prevention behavior in toddlers based on the results of previous studies. This study uses the Systematic Literature Review (SLR) method with the PRISMA approach. Articles were searched in PubMed, ScienceDirect, and Google Scholar using keywords on maternal knowledge, diarrhea, and prevention behavior in toddlers with Boolean operators (AND/OR). Inclusion criteria included quantitative, qualitative, or mixed-methods studies published from 2020–2025, full-text, and addressing the relationship between maternal knowledge and diarrhea prevention or incidence. Fifteen eligible articles were analyzed descriptively. The results of the study showed that maternal knowledge levels were significantly associated with diarrhea prevention behaviors, diarrhea management practices, the implementation of clean and healthy living behaviors (PHBS), and the incidence of diarrhea in toddlers. Mothers with good knowledge levels tended to implement more optimal prevention behaviors and had toddlers with a lower risk of diarrhea. However, the effectiveness of knowledge implementation is influenced by maternal characteristics, socioeconomic conditions, and sanitation availability. Maternal knowledge plays a crucial role in preventing diarrhea in toddlers through preventive behaviors and reducing its incidence. Thus, sustainable health education supported by adequate sanitation and environmental conditions must be improved to reduce diarrhea incidence in toddlers.